PERAN MEDIA SOSIAL DALAM KOMUNIKASI PUBLIK BERBASIS KHALAYAK BERDASARKAN NILAI KE-ISLAMAN - Murtadlo, Ali (Universitas Riau, 2025)
Audience-based public communication places the audience at the center of the communication process, focusing on understanding their characteristics and needs to achieve message effectiveness. This study aims to analyze the role of social media in spreading Islamic values, considering that digital platforms such as Instagram and YouTube are effective means of da'wah for the younger generation. The research method uses a descriptive qualitative approach through literature studies, with data obtained from books, journals, and related articles. The results of the study show that social media facilitates the spread of Islamic messages creatively, two-way interaction, education, and the development of a solid Muslim community. However, challenges such as hoaxes and negative content require good media literacy. In conclusion, social media, if used wisely, can be a powerful da'wah tool in the context of public communication based on Islamic values.